Navigating Village Credit Institutions Based On Sad Kerthi Loka Bali In Buleleng Regency - I Made Mai Noval; A.A.N Oka Suryadinatha Gorda; A.A.N Eddy Supriadinata Gorda (University of Merdeka Malang, 2022)
This study examines how the village credit institution implements the local wisdom of Sad Kerthi in the form of the vision of